Pengaruh Good Corporate Governance dan Kinerja Keuangan Terhadap Harga Saham Perusahaan Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2011-2018 - Nafisah Nurulrahmatiah; Aliah Pratiwi; nurhayati (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2020)
This study aims to determine how much influence the Good Corporate Governance and financial performance on stock prices on food and beverage sector companies listed on the Stock Exchange. Good corporate governance can be seen from the board of directors, independent commissioners, and institutional ownership, in addition one of the ratios which can be used to see financial performance. The share price is identified by the closing price when the financial statements are published. The results showed that the board of directors, independent commissioners, institutional ownership and ROE had an influence on the stock prices of food and beverage companies listed on the Indonesia Stock Exchange in 2011-2018.